“Days of vengeance, days of mercy”: experiencing violence and divine providence in British North America, 1744–1757 - Loganbill, Alec Taylor (Kansas State University, 2021)
This thesis addresses the ways a group of clergymen and lay people in colonial British North America used “providentialism,” or the effort to explain the divine meaning behind worldly events, as a means of understanding their experience of war during King George’s War (1744–1748) and the early stages of the French and Indian War (1754–1757). Rather than surveying the tremendous number and range of providential interpretations coming from pulpits throughout the Atlantic world, I closely follow the interconnected lives of members of the personal network of Jonathan Edwards, a key theologian and preacher of the Great Awakening, detailing how they perceived and responded to providence during times of violence, and how they interacted with and affected each other through a shared providentialism. Edwards’s network included evangelical ministers in New England and throughout the British Atlantic; family members, including his daughter Esther Edwards Burr and her husband Aaron Burr; government and military officials like Governor William Shirley and Colonel Israel Williams of the Massachusetts colony; and the lay members of his congregations, most notably Seth and Mary Pomeroy of Northampton. In reconstructing this personal network of religious people, lay and ordained, through their letters, diaries, and sermons, I situate personal connections and providential beliefs and practices within the existing religious, political, and social milieu. While social class, educational attainment, and gender all affected the manner in which my subjects constructed or drew on providential themes, their shared religious culture and the collectively-experienced events of war created the space and means for them to find meaning in the violence that surrounded them.
Keywords: Colonial American history; Religious history; King George's War; French and Indian War; Divine providence; Jonathan Edwards